Kolmogorov widths of anisotropic function classes and finite-dimensional balls - Vasil’eva, Anastasia (Eurasian Mathematical Journal, 2024)
In this paper, we obtain order estimates for the Kolmogorov widths of anisotropic periodic Sobolev and Nikol’skii classes, as well asanisotropic finite-dimensional balls.